تقييم مستوى جودة الخدمات الصحية في المؤسسات الاستشفائية العمومية لولاية الشلف باستخدام نموذج "servperf" - حواس, مولود; بن هراوة, العالية (جامعة الوادي University of Eloued, 2021)
This study aims at assessing the quality of health services in the public hospitals in Chlef using the "SERVPERF" model. This was done through a field study. The study found that the level of quality of health services provided to patients in the hospitals under study was medium, and there were no statistical significant differences in the quality of health services due to demographic characteristics except for the variable level of education.
Assessing the Quality of Health Services in The Public Hospitals of Chlef using the"SERVPERF" Model
مقال
Keywords: جودة ; خدمات صحية ; جودة الخدمات الصحية ; نموذج "SERVPERF" ; مؤسسات استشفائية عمومية.